2015
DOI: 10.1245/s10434-015-4547-7
|View full text |Cite
|
Sign up to set email alerts
|

Is Sentinel Lymph Node Dissection Warranted for Patients with a Diagnosis of Ductal Carcinoma In Situ?

Abstract: Background Positive sentinel lymph node (SLN) findings in DCIS range from 1–22% but have unknown biologic significance. We sought to identify predictors of positive SLNs and to assess their clinical significance in patients initially diagnosed with DCIS. Methods We identified 1234 patients with an initial diagnosis of DCIS who underwent SLN dissection (SLND) at our institution (1997–2011). Positive SLN findings were categorized as isolated tumor cells (ITCs) (≤0.2mm), micrometastases (>0.2–2mm), or macrometa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
57
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 40 publications
7
57
0
6
Order By: Relevance
“…Sentinel lymph node biopsy is not the standard of care in DCIS of the breast . Indeed, various studies demonstrated a widely variable proportion of DCIS patients with SLNB positive for metastatic disease, ranging from 1% to 22% . Therefore, the role of SLNB procedure in such patients remains controversial, but anyway there is a very small subset of DCIS patients whose clinical management could be changed by SLNB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sentinel lymph node biopsy is not the standard of care in DCIS of the breast . Indeed, various studies demonstrated a widely variable proportion of DCIS patients with SLNB positive for metastatic disease, ranging from 1% to 22% . Therefore, the role of SLNB procedure in such patients remains controversial, but anyway there is a very small subset of DCIS patients whose clinical management could be changed by SLNB.…”
Section: Discussionmentioning
confidence: 99%
“…First, foci of invasive ductal carcinoma could have been missed by the pathologist on tissue sampling of extensive surgical specimens, such as in case of microinvasive disease on a mastectomy, despite accurate staining with p63 . Second, it was recently reported that epithelial cells could migrate by lymphatic flux from tumor to the sentinel node, especially after invasive procedures such as breast biopsy; this fact has been associated to the diagnosis of axillary involvement in pure DCIS . Third, it was recently pointed out that a particular subset of DCIS lesions could have unknown metastatic potential due to a peculiar biological behavior; this statement was assumed after the observation that in some cases a distant recurrence was encountered in patients previously treated for DCIS, without any evidence of invasive cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Some series in which the axilla was evaluated by full axillary lymph node dissection (FAD) showed a metastases rate lower than 1% . The theory of benign mechanical transport of breast epithelial cells may support the presence of DCIS in the axillary lymph nodes …”
Section: Discussionmentioning
confidence: 99%
“…Routine use of sentinel lymph node dissection (SLND) in DCIS is not recommended except for patients at high‐risk for invasive disease, particularly for those undergoing breast‐conserving surgery . Nowadays in case of performing a mastectomy due to DCIS, SLN is the standard of care …”
Section: Discussionmentioning
confidence: 99%
“…4,10,12,13 Reported rates for performance of SLNB for DCIS range from 21 to 97 %, but these rates are reported primarily from single-institution studies examining predictors of SLNB positivity, which select for tumors with high-risk characteristics. 6,[14][15][16] In 2010, the rate was 17.8 % for lumpectomy patients and 67.1 % for mastectomy patients in the Surveillance, Epidemiology, and End Results (SEER) database, although this was based on the number of lymph nodes examined rather than the specific type of axillary surgery. 17 In 2012, the National Cancer Data Base (NCDB) began collecting information on whether SLNB or axillary lymph node dissection (ALND) was performed in addition to the number of nodes removed.…”
mentioning
confidence: 99%